1999
DOI: 10.1021/je9802165
|View full text |Cite
|
Sign up to set email alerts
|

Medium Effect on the Acid Dissociation Constants of Some Heterocyclic Azo Compounds

Abstract: The effect of different organic solvent + water mixtures on the acid dissociation constants of protonated 5-amino-4-(arylazo)-3-methyl-1-phenylpyrazole derivatives were studied. The organic solvents used are methanol, ethanol, acetone, and dimethylformamide. The results obtained were discussed in terms of the solvent characteristics.The pK BH + values of the dyes in question were determined and found to depend on both the amount and nature of the organic cosolvent. The decrease of the pK BH + values as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It was found that they exist in the keto form in solids state while in solution the enol form predominates. 1,14 The visible absorption spectra of 8-[p-substituted phenylazo]-2,4-dimethylpyrazolo[1,5-a]pyrimidine-7(6H)-one derivatives in universal buffer solutions containing different proportions of an organic solvent (methanol, ethanol, acetone, and DMF) show mainly two bands (Figure 1). The shorter wavelength band, appearing at low pH* values (pH* < 6.0), represents absorption by the nonionized species, whereas the longer wavelength band, observed at higher pH* values (pH* > 8.8), is due to the absorption by ionized species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that they exist in the keto form in solids state while in solution the enol form predominates. 1,14 The visible absorption spectra of 8-[p-substituted phenylazo]-2,4-dimethylpyrazolo[1,5-a]pyrimidine-7(6H)-one derivatives in universal buffer solutions containing different proportions of an organic solvent (methanol, ethanol, acetone, and DMF) show mainly two bands (Figure 1). The shorter wavelength band, appearing at low pH* values (pH* < 6.0), represents absorption by the nonionized species, whereas the longer wavelength band, observed at higher pH* values (pH* > 8.8), is due to the absorption by ionized species.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge of the p K a is considered to be of interest for organic and inorganic compounds because it has a significant role in many chemical reactions. Therefore, numerous works have been devoted to the determination of p K a values of the different azo compounds. The widespread application of the azo compounds as dyes; acid−base, redox, and metallochrome indicators; or histological stains has attracted many studies of their acid−base properties. In continuation of our studies on the acid−base properties of azo compounds, ,, we have investigated the medium effect on the ionization constants of some arylazopyrazolopyrimidine derivatives by the study of the electronic spectra of the compounds in aqueous buffer solutions containing varying proportions of organic solvents of different polarities, such as methanol, ethanol, acetone, and dimethylformamide (DMF). The p K a values have been determined and discussed in terms of solvent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The dissociation constant was measured by the potentiometric titration method. 2 A cylindrical-jacketed glass vessel (100 mL) maintained at a desired temperature by water circulated from a water bath with a thermoelectric controller (type 501, China) was placed on a magnetic stirrer. The jacket temperature could be maintained within ( 0.05 K of the required temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, the pI is greatly influenced by the solvents in the crystallization system. 2 To design an optimized crystallization process pertinent in industrial production, it is necessary to determine the pI and solubility values in various solvent systems. 3 In this work, the dissociation constant and solubility in water + 1-butanol + butyl acetate at (278.15 to 293.15) K was determined.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of p K a is considered to be of great interest for organic and inorganic compounds, because it has a significant role in many chemical reactions. Therefore, numerous works have been devoted to the determination of p K a values of different azo compounds. From another point of view, in the past decades azo dye chemistry based on heterocyclic systems received a lot of interest. In a broad sense, many of heterocyclic azo dyes show dramatic bathochromic shifts combined with brilliance of shade and high tinctorial strength compared with the cases of conventional anthraquinone dyes and aminobenzene azo dyes …”
Section: Introductionmentioning
confidence: 99%